2022
DOI: 10.1128/mbio.00422-22
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of a cis -Acting SNP That Controls Type VI Secretion in Vibrio cholerae

Abstract: Organisms sense external cues with regulatory circuits that trigger the production of transcription factors, which bind specific DNA sequences at promoters (“ cis ” regulatory elements) to activate target genes. Mutations of transcription factors or their regulatory elements create phenotypic diversity, allowing exploitation of new niches.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…Importantly, for several phenotypes, an increased fitness has been demonstrated for heterogenous populations, supporting the idea that bacteria can use bet-hedging strategies to maximize survival [67]. Notably, the observed sporadic (or stochastic) VxrAB-dependent T6SS production phenotype differed significantly from the T6SS status of environmental and non-pandemic V. cholerae strains, which contain a deterministic SNP upstream of vipA [36,37]. Indeed, strains carrying this SNP, as well as TfoX-/TfoY-producing 7PET strains, show almost uniform T6SS production within the population consistent with increased T6SS transcript levels compared to those in WT 7PET strains, as demonstrated previously through RNA sequencing (RNA-seq) [24,28,36].…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Importantly, for several phenotypes, an increased fitness has been demonstrated for heterogenous populations, supporting the idea that bacteria can use bet-hedging strategies to maximize survival [67]. Notably, the observed sporadic (or stochastic) VxrAB-dependent T6SS production phenotype differed significantly from the T6SS status of environmental and non-pandemic V. cholerae strains, which contain a deterministic SNP upstream of vipA [36,37]. Indeed, strains carrying this SNP, as well as TfoX-/TfoY-producing 7PET strains, show almost uniform T6SS production within the population consistent with increased T6SS transcript levels compared to those in WT 7PET strains, as demonstrated previously through RNA sequencing (RNA-seq) [24,28,36].…”
Section: Discussionmentioning
confidence: 67%
“…In this context, we recently reported the experimental identification of a single-nucleotide polymorphism (SNP) located in an intergenic region within the primary T6SS cluster of V. cholerae [36], which was concomitantly also identified by others using a bioinformatic approach [37]. We demonstrated that the exchange of this SNP (e.g.…”
Section: Introductionmentioning
confidence: 95%
“…All V. cholerae mutant strains were made using the pKAS allelic exchange system described by Skorupski et al using pKAS32 (Skorupski & Taylor, 1996). JT101 and SN598 (Table S1) were described in previous studies (Ng et al, 2022;Thomas et al, 2017). CZ005 and CZ006 were generated through an insertion of a spectinomycin resistance cassette into the lacZ gene of JT101 and SN598, respectively.…”
Section: Mutant Constructionmentioning
confidence: 99%
“…In the current pandemic strains of V. cholerae , this activation is orchestrated by the TfoX master regulator once the bacteria reach a high cell density state [42,43,45,46]. In environmental V. cholerae isolates, the T6SS machinery is in a state of constant activity [20,4750], representing an immediate risk for T6SS-associated harm in case cell-to-cell contact in established. Therefore, bacteria must distinguish between nearby individuals before intentionally initiating cell-to-cell contact.…”
Section: Introductionmentioning
confidence: 99%